Brand love y lealtad de marca universidad-estudiantes: Revisión sistemática de la literatura bajo el enfoque PRISMA 2013-2023 - Cieza Esteban, Augusto Antonio (2025)
The purpose of this systematic literature review was to analyze the impact of brand love and brand loyalty constructs on the relationship between universities and their students during the period 2013-2023, and to identify strategies to strengthen this relationship. The PRISMA 2020 approach was used to collect 21 relevant scientific papers from various academic databases such as Web of Science, EBSCOhost, ProQuest and Redalyc. The results showed that brand love and brand loyalty strengthen the emotional bond between the institution and its students. Factors such as developing emotional connections, meeting student expectations, and providing quality education had a positive impact on this bond. Effective strategies for enhancing both constructs in areas such as student experience, university brand image, and service communication were also identified. The study concludes by recommending that high academic standards be maintained along with comprehensive student support, and that an emotional connection be fostered from the early years of education to consolidate brand love and brand loyalty. In addition, it suggests that other moderating factors should be explored in future research.